Low vision services for children in Tanzania - Elizabeth Kishiki; Paul Courtright (Community Eye Health Journal, 2012)
The Kilimanjaro Centre for Community Ophthalmology (KCCO) has been involved in a five-year pilot project to improve low vision services for children in Tanzania. Low vision services were limited to a few tertiary hospitals and were accessible to only a few children.